The Relationship between Native Americans and the Chinese: Representation of the Formation of National Identity in the Short Story Sin Po of the 1940s - Agus Sri Danardana; sartika sari; Sri Yono; Rafiqah Yusna Siregar (English Language Teaching Prima Journal (ELT), 2026)
ABSTRACT This study examines the formation of Chinese national identity in short stories published in the Sin Po newspaper during the 1930s and 1940s, arguing that this identity emerges most clearly in the relationship depicted between the Chinese and the indigenous Indonesian population. Using a qualitative sociology-of-literature approach with content analysis, it reads the stories as social documents and interprets them through Castells's typology of identity construction—legitimizing, resistance, and project identity—alongside theories of imagined and diasporic national identity. The analysis identifies three modes of identification: a legitimizing identity imposed by colonial racial classification (